زكاة رواتب الموظفين وتطبيقاتها في إندونيسيا: دراسة فقهية تحليلية - رمضان، تيكوه سوتيا إسما (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study aims to explain the opinions of contemporary Muslim scholars pertaining to zakat on the salaries of employees, as well as to study its implementation in the National Board of Zakat of West Java Province. Additionally, it also discusses the juristic problems and solutions that have remained unsolved. Three approaches were employed in this study; firstly, the inductive method which seeks to trace the contemporary scholars' views in zakat on employees' salaries and its application in Indonesia. Secondly, the analytical method was employed in order to review and appraise those views and then, recommend which view is appropriate and widely useful for the society. Additionally, it is equipped with analyses of the defects of zakat implementation in the National Board as mentioned earlier. Finally, the field-based method was conducted through interviews with stakeholders with the aim to comprehend the way the National Board collects and distributes zakat. The study has reached a number of conclusions. The case of zakat on the salaries of employees remains debatable among contemporary Muslim intellectuals due to the absence of texts which are valid and explicit. However, according to their arguments, the views contending that it is compulsory are more acceptable than the others. Moreover, the National Board of Zakat in West Java Province is able to collect zakat on employees' salaries by deducting gross income and then distributing it directly or materializing it in some productive programs, and the most significant juristic issue in this case is hastening zakat payment before its nisab.